Assessing therapeutic safety and efficacy of Pazopanib, Pembrolizumab plus Axitinib and Nivolumab plus Ipilimumab in Renal Cell Carcinoma: a systematic review and meta-analysis - Shawn, Ibna Hasan (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.